Assessment of Barriers in Initiation and Completion of Isoniazid Preventive Therapy among Household Child Con-tacts of Pulmonary TB Patients in Delhi: A Mixed Method Study - Ahmed, Faheem; Malik, Tazean Zahoor; Islam, Farzana; Muzaffar, Areeba (National Journal of Community Medicine, 2020)
Background: Young children (aged < 6 years) in contact with Sputum positive TB adults are often infected with Mycobacterium tuberculosis and once infected are at higher risk of progression to TB disease than adults. Objectives: The study was conducted To find out the proportion of < 6 years of age children having household contact of a pulmonary TB patient, screened, initiated, and completed IPT in the year 2019 and to find out the barriers for not completing/taking IPT. Methodology: A mixed-method study was conducted during July–September 2019 among household contacts of < 6 years of age of sputum positive pulmonary TB patients attending a DOT centre in South – East Delhi. Results: A total of 52 household contacts of less than 6 years of age were identified. Whereas 65% of the study population was aware of IPT, only 26.9% of individuals were on IPT out of the total study population and only 4 % had completed the IPT. On qualitative analysis, most of them informed that the DOTS provider didn’t emphasize them about IPT. Some of them felt that it isn’t required since the child does not have the disease. Conclusion: Adherence to IPT is low. The dearth of IEC activities in the study area adds to this burden. Hence prompt IEC activities and adequate training of DOT providers for initiation and adherence of IPT is the need of the time.